Understanding the reactivity and regioselectivity of [3 + 2] cycloaddition reactions between substituted nitrile oxides and methyl acrylate. A molecular electron density theory study. Issue 24 (14th August 2017) - Ndassa, Ibrahim Mbouombouo; Adjieufack, Abel Idrice; Mbadcam Ketcha, Joseph; Berski, Slawomir; Ríos‐Gutiérrez, Mar; Domingo, Luis R.
Abstract: The [3 + 2] cycloaddition (32CA) reactions of three nitrile oxides (NOs) (R‐CNO; R = Ph, CO2 Me, and Br) with methyl acrylate (MA) have been theoretically studied within the molecular electron density theory. Topological analysis of the electron localization function of these NOs permits to establish that they will participate in zw‐type 32CA reactions. Analysis of the conceptual DFT indices indicates that these zw‐type 32CA reactions will have a low polar character as a consequence of the relatively low electrophilic character of MA and the low nucleophilic character of NOs, in agreement with the global electron density transfer computed at the corresponding TSs. The activation enthalpies associated with these 32CA reactions range from 8.2 to 12.7 kcal·mol −1 . The presence of the bromide atom provokes the larger acceleration. While the 32CA reaction involving the CO2 Me substituted NO is highly ortho regioselective, the other two reactions are poorly ortho regioselective. A bonding evolution theory study of the more favorable ortho regiosiomeric channel associated with the 32CA reaction involving the Br substituted NO indicates that this reaction is associated to a nonconcerted two‐stage one‐step mechanism, in which the activation energy is mainly related to the initial rupture of the CN triple bond of the NO. Abstract : Density functional theory calculations provide insight into the reaction mechanism and regioselectivity of the [3 + 2] cycloaddition (32CA) reactions of three substituted nitrile oxides with methyl acrylate (MA). The presence of a bromide atom accelerates these zwitterionic‐type 32CA reactions. The ortho regioselectivity depends on the nature of the R group. A bonding evolution theory study of the 32CA reaction involving the Br substituted nitrile oxide indicates that these reactions take place through a nonconcerted two‐stage one‐step mechanism.